2021
DOI: 10.1136/emermed-2020-210450
|View full text |Cite
|
Sign up to set email alerts
|

Retention of doctors in emergency medicine: a scoping review of the academic literature

Abstract: IntroductionWorkforce issues prevail across healthcare; in emergency medicine (EM), previous work improved retention, but the staffing problem changed rather than improved. More experienced doctors provide higher quality and more cost-effective care, and turnover of these physicians is expensive. Research focusing on staff retention is an urgent priority.MethodsThis study is a scoping review of the academic literature relating to the retention of doctors in EM and describes current evidence about sustainable c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 69 publications
2
25
0
Order By: Relevance
“…It was found that average monthly income was negatively related to turnover intention among physicians in emergency department. It is probably due to the lower average monthly income may not cover living needs for physicians in emergency department, so the physicians who have a lower average monthly income were more likely to leave emergency department, which was in line with previous study [ 30 ].…”
Section: Discussionsupporting
confidence: 89%
“…It was found that average monthly income was negatively related to turnover intention among physicians in emergency department. It is probably due to the lower average monthly income may not cover living needs for physicians in emergency department, so the physicians who have a lower average monthly income were more likely to leave emergency department, which was in line with previous study [ 30 ].…”
Section: Discussionsupporting
confidence: 89%
“…Turnover is considered a negative internal indicator by most organizations and the common belief is that employees leave their jobs due to dissatisfaction and other negative reasons. Several studies describe burnout as a reason or mediator of high turnover rates among healthcare workers that should be kept at low levels to increase employee retention ( Neale, 1991 ; Leiter and Maslach, 2009 ; Mahoney et al, 2020 ; Shields et al, 2020 ; Darbyshire et al, 2021 ; Kim and Kim, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, investigative focus has turned towards retention, or looking at what conditions support continued employment (e.g. Darbyshire et al., 2021). Ensuring that careers are sustainable, with ‘less than full time’ training, more flexible pathways, and a hard look at some of the more problematic elements of work‐life balance such as rota management have become key elements of the narrative around minimising turnover and keeping doctors in the NHS.…”
Section: Literature Reviewmentioning
confidence: 99%